Ahlquist, Irving (audio interview #4 of 5) - Ahlquist, Irving (b. 1916 - d. 2004); Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This is the fourth of five interviews conducted in Ahlquist's office in the CSULB History Department. The audio quality of this interview is good. 4/14/1978